2019
DOI: 10.1136/bmj.l1945
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of obstructive coronary artery disease using computed tomography angiography in patients with stable chest pain depending on clinical probability and in clinically important subgroups: meta-analysis of individual patient data

Abstract: Objective To determine whether coronary computed tomography angiography (CTA) should be performed in patients with any clinical probability of coronary artery disease (CAD), and whether the diagnostic performance differs between subgroups of patients. Design Prospectively designed meta-analysis of individual patient data from prospective diagnostic accuracy studies. Data sources Medline, Embase, and Web of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 53 publications
(69 reference statements)
3
87
0
2
Order By: Relevance
“…5 , 12 A recent meta-analysis based on Diamond and Forrester pre-test probabilities demonstrated CTCA to be most accurate in patients with a pre-test probability between 7% and 67%. 18 A specific threshold is not stated in the latest guidelines but applying a 50% threshold to the current pre-test probabilities would infer that nearly all patients should have CTCA where possible. The recommendation for functional testing in patients with >50% pre-test probability is largely based on the recognized potential for discordance between anatomical stenosis severity and the haemodynamic effects of a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 12 A recent meta-analysis based on Diamond and Forrester pre-test probabilities demonstrated CTCA to be most accurate in patients with a pre-test probability between 7% and 67%. 18 A specific threshold is not stated in the latest guidelines but applying a 50% threshold to the current pre-test probabilities would infer that nearly all patients should have CTCA where possible. The recommendation for functional testing in patients with >50% pre-test probability is largely based on the recognized potential for discordance between anatomical stenosis severity and the haemodynamic effects of a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) is part of the routine TAVI planning for sizing the valve prosthesis and assessment of the access route [7]. Moreover, CT is used to rule out significant coronary stenosis with low to intermediate pre-test probability for coronary artery disease (CAD) [8]. A holistic CT evaluation of aorta, peripheral vessels and coronary arteries pre-TAVI procedure could lead to a reduction of unnecessary ICA and, consequently, of cumulative radiation dose, contrast volume and risk management.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies using coronary CTA for diagnosis of stable CAD in the elderly exist in the literature [ 50 , 51 , 52 , 53 , 54 ]. A meta-analysis of 5332 patients, including 462 patients aged >75 years, reported a sensitivity of coronary CTA for diagnostic of obstructive CAD of 94% and a specificity of 77%, alongside a PPV of 83%, NPV of 91%, LR+ of 4.1 and LR− of 0.08 [ 54 ]. The authors revealed reduced efficacy of coronary CTA for the diagnosis of obstructive coronary atherosclerosis in patients aged >75 years compared to other age groups.…”
Section: Coronary Computed Tomography Angiography For Diagnosis Ofmentioning
confidence: 99%
“…A meta-analysis of 18 studies reported a sensitivity of 98%, a specificity of 82%, a PPV of 91% and an NPV of 99% [ 59 ]. Another meta-analysis including 65 studies reported a CTA sensitivity of 95% and a specificity of 79% [ 54 ]. The efficacy of CTA in CAD diagnostics was not dependent on the type of chest pain.…”
Section: Coronary Computed Tomography Angiography For Diagnosis Ofmentioning
confidence: 99%